2016
DOI: 10.1007/s40279-016-0629-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuromechanical Modulation of the Achilles Tendon During Bilateral Hopping in Patients with Unilateral Achilles Tendon Rupture, Over 1 Year After Surgical Repair

Abstract: These results suggest that the repaired ruptured AT can be compliant and have insufficient Young's modulus, which can influence mechanical responses in muscle activities. The modulation of agonist-antagonist muscle activities corresponding to the different levels of stiffness between the LEG and the LEG may not be fully functioning during the pre-activation phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Similar to the present study, they reported increased amplitude of activity in the soleus and no differences between sides in the medial gastrocnemius. 23 The results of the present study further suggest that the lateral and medial gastrocnemii do not activate similarly in individuals with Achilles tendon rupture, supporting continued investigation of the individual contributions of each of these muscles. Decreases in medial gastrocnemius but not lateral gastrocnemius cross sectional area further support the notion that the gastrocnemii are not affected by Achilles tendon rupture in the same way and should be considered separately.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Similar to the present study, they reported increased amplitude of activity in the soleus and no differences between sides in the medial gastrocnemius. 23 The results of the present study further suggest that the lateral and medial gastrocnemii do not activate similarly in individuals with Achilles tendon rupture, supporting continued investigation of the individual contributions of each of these muscles. Decreases in medial gastrocnemius but not lateral gastrocnemius cross sectional area further support the notion that the gastrocnemii are not affected by Achilles tendon rupture in the same way and should be considered separately.…”
Section: Discussionsupporting
confidence: 63%
“…A prior study by Oda et al, investigated side to side differences in soleus and medial gastrocnemius amplitude of activation during a bilateral hopping task. Similar to the present study, they reported increased amplitude of activity in the soleus and no differences between sides in the medial gastrocnemius .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations